NUTRITIONAL STATUS AND QUALITY OF LIFE OF PATIENTS WITH LYMPHOMA - Vukasović, Vanja D; Đurašinović, Vladislava (Medicinski podmladak, 2019)
Introduction: Treatment of malignancies nowdays has to control the disease and to achieve an adequate quality of life. Malnutrition at diagnosis and treatment is not rare, but is not determined regularly. Aim: Determination of the frequency of malnutrition during chemotherapy and analysis of the quality of life in relation to the characteristics of the patients and type of lymphoproliferative diseases. Material and methods: The study included 30 men and 20 women treated at the Clinic for hematology KCS between November 2017 and February 2018 with lymphoproliferative disease on chemotherapy or immunochemotherapy. Malnutrition Nutritional Risk Screening 2002 (NRS 2002) and the Mini Nutritional Assessment (MNA) were used for the assessment of malnutrition. Quality of life was assessed by Fact-Lym. Results: The average age of respondents was 53.5 (95% CI 49.8 to 57.2) years. 64% of all patients were on the initial treatment, 36% were in relapse. According to NRS 2002 questionnaire 23 (46%) patients were malnourished, and according to MNA 32 (64%) patients were malnourished. A significantly higher frequency of malnourished patients was in the group whose CRP ≥ 10 mg/l (p = 0.010 for NRS 2002 and p = 0.036 for MNA). All patients with ECOG PS ≥ 3 were malnourished according to MNA. The overall quality of life did not differ with respect to patient characteristics (gender, age < 70 vs ≥ 70 years, disease stage, indolent vs aggressive disease, ECOG PS ≤ 2 vs ≥ 3, NRS 2002 ≤ 2 vs ≥ 3, MNA ≤ 11 vs ≥ 12, CRP < 10 vs ≥ 10 mg/l). A sub-category - physical condition was significantly various in a group of malnourished and non-malnourished patients estimated by NRS 2002 (p = 0.01). Conclusion: Nutritional status of patients with lymphoproliferative disease on chemotherapy or immunochemotherapy is damaged in about half of patients. Quality of life, especially the physical condition was significantly worse in the group of malnourished patients.